The transcription factor OCT6 promotes the dissolution of the naïve pluripotent state by repressing Nanog and activating a formative state gene regulatory network - Waisman, Ariel (2024)
In the mouse embryo, the transition from the preimplantation to the postimplantation epiblast isgoverned by changes in the gene regulatory network (GRN) that lead to transcriptional, epigenetic,and functional changes. This transition can be faithfully recapitulated in vitro by the differentiationof mouse embryonic stem cells (mESCs) to epiblast-like cells (EpiLCs), that reside in naïve andformative states of pluripotency, respectively. However, the GRN that drives this conversion isnot fully elucidated. Here we demonstrate that the transcription factor OCT6 is a key driver of thisprocess. Firstly, we show that Oct6 is not expressed in mESCs but is rapidly induced as cells exit thenaïve pluripotent state. By deleting Oct6 in mESCs, we find that knockout cells fail to acquire thetypical morphological changes associated with the formative state when induced to differentiate.Additionally, the key naïve pluripotency TFs Nanog, Klf2, Nr5a2, Prdm14, and Esrrb were expressedat higher levels than in wild-type cells, indicating an incomplete dismantling of the naïve pluripotencyGRN. Conversely, premature expression of Oct6 in naïve cells triggered a rapid morphologicaltransformation mirroring differentiation, that was accompanied by the upregulation of theendogenous Oct6 as well as the formative genes Sox3, Zic2/3, Foxp1, Dnmt3A and FGF5. Strikingly, wefound that OCT6 represses Nanog in a bistable manner and that this regulation is at the transcriptionallevel. Moreover, our findings also reveal that Oct6 is repressed by NANOG. Collectively, our resultsestablish OCT6 as a key TF in the dissolution of the naïve pluripotent state and support a modelwhere Oct6 and Nanog form a double negative feedback loop which could act as an important togglemediating the transition to the formative state.